A comparative study of lithium and sodium salts in PAN-based ion conducting polymer electrolytes - Osman, Z.; Isa, K.B.M.; Ahmad, A.; Othman, L. (2010)
The conducting polymer electrolyte films consisting of polyacrylonitrile (PAN) as the host polymer, lithium triflate (LiCF(3)SO(3)) and sodium triflate (NaCF(3)SO(3)) as inorganic salts were prepared by the solution-cast technique. The pure PAN film was prepared as a reference. The ionic conductivity for the films is characterized using impedance spectroscopy. The room temperature conductivity for the PAN + 26 wt. LiCF(3)SO(3) film and the PAN + 24 wt. NaCF(3)SO(3) film is 3.04 x 10(-4) S cm(-1) and 7.13 x 10(-4) S cm(-1), respectively. XRD studies show that the complexation that has occurred in the PAN containing salt films and complexes formed are amorphous. The FTIR spectra results confirmed the complexation has taken place between the salt and the polymer. These results correspond with surface morphology images obtained from SEM analysis. The conductivity-temperature dependence of the highest conducting film from PAN + LiCF(3)SO(3) and PAN + NaCF(3)SO(3) systems follows Arrhenius equation in the temperature range of 303 to 353 K. The PAN containing 24 wt. LiCF(3)SO(3) film has a higher ionic conductivity and lower activation energy compared to the PAN containing 26 wt.LiCF(3)SO(3) film. These results can be explained based on the Lewis acidity of the alkali ions, i.e., the interaction between Li(+) ion and the nitrogen atom of PAN is stronger than that of Na(+) ion.